Nexos entre México y Europa Centro-Oriental - Szente-Varga, Mónika (Acta Hispanica, 2012)
The first diplomatic and consular relations were established between Mexico and theHabsburg Empire in the 1800 s, motivated basically by commerdal reasons and dynasticinterests. These got to an abrupt end with the execution of Emperor Maximilian in Querétaro in1867, and diplomatic relations were resumed only decades later, in 1901, which is, in fact, ourstarting point. This essay examines the development of diplomatic relations between Mexico andCentral-Eastern Europe from the beginning of the 20'' centuiy until nowadays. It is divided intochronological chapters, where we study bilateral relations in the coordinates of the followingperiods: beginning of the century, the period between the two world wars, the Second World War,Cold War and recent years. The investigation in based on documents of the Ministry of ForeignAffairs of Mexico (SRE-AHD) and of the Hungarian National Archive (MOL).